2004
DOI: 10.1097/01.ju.0000114303.17198.37
|View full text |Cite
|
Sign up to set email alerts
|

Computer Aided Learning Versus Standard Lecture for Undergraduate Education in Urology

Abstract: According to this study computers and multimedia programs can be used for undergraduate education in urology, providing that direct contact with an instructor is concomitantly offered to students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 11 publications
2
33
0
Order By: Relevance
“…Our findings are in agreement with other published studies that use J AM ACAD DERMATOL VOLUME 59, NUMBER 2 multimedia teaching techniques for urology, surgical techniques, and neuroanatomy. 11,20,21 There are several possible reasons that our study showed no significant difference between teaching methods. The study only tested medical students on dermatology morphology visual recognition and appropriate use of terminology which was only a small part of the overall course.…”
Section: Discussionmentioning
confidence: 59%
“…Our findings are in agreement with other published studies that use J AM ACAD DERMATOL VOLUME 59, NUMBER 2 multimedia teaching techniques for urology, surgical techniques, and neuroanatomy. 11,20,21 There are several possible reasons that our study showed no significant difference between teaching methods. The study only tested medical students on dermatology morphology visual recognition and appropriate use of terminology which was only a small part of the overall course.…”
Section: Discussionmentioning
confidence: 59%
“…Few randomised controlled trials have been performed in CAL medical education and many of those that have been performed look at small subunits of the overall medical corriculum[1] Of the trials that have been performed on CAL, the evidence suggests a high information assimilation rate among medical students[5,10-13] Seabra et al wanted to explore the outcome of replacing lectures completely with a CAL programme and demonstrated that computer aided learning could achieve similar results to standard lectures[14] Some evidence suggests that although the gain in knowledge is similar following computer or traditional instruction, the time required to achieve these similar results is less when the student uses the computer aided instruction[15]…”
Section: Discussionmentioning
confidence: 99%
“…Most papers described the use of technology in their medical school and few measured the impact of learning. The literature highlighted the feature of mobile learning as bridging distances, creating links, preventing feelings of isolation in students [5][6][7][8][9], and challenging faculty to develop skills to incorporate and troubleshoot technology on distributed sites and produce e-resources [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%